THE PROBLEM OF NON-FORMAL ADULT EDUCATION QUALITY SERVICE PROVISION IN LOCAL MUNICIPALITIES OF LITHUANIA - Zemaitaityte, Irena; Petrauskiene, Alina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article analyzes one of the most important and, simultaneously, the most problematic factors in the development of adult education as the implementation quality of Non-formal Adult Education (hereinafter NAE) at the local government level. The aim of this article is to reveal the understanding of Lithuanian municipal non-formal adult education coordinators about improving the quality of non-formal adult education services. The study has centered on a focus group (12 people) in which Lithuanian non-formal adult education coordinators from different municipalities discussed and shared their diverse opinions. According to the focus group participants, the quality assessment of educational services in local communities is required by the institutions or foundations financing the services, which at the same time indicate the criteria for assessing the quality of services and their fulfillment when reporting on the implementation of educational services. According to the participants of the study, Lithuanian municipalities should have more power in decision making on planning educational programs and services to meet the needs of the local population; they should expect stable funding guarantees from state institutions, which must first and foremost be interested in improving non-formal education services quality assessment.